A heavy rare earth-free high-performance lanthanum-cerium-containing rare earth permanent magnet and its manufacturing method

By rationally controlling the composition of the permanent magnet and doping Nb and Zr elements, and optimizing the grain boundary phase distribution, the problem of adding heavy rare earth elements to existing lanthanum-cerium magnets has been solved, the preparation of high-performance magnets has been achieved, the production cost has been reduced and the scope of applications has been broadened. market application.

CN117747233BActive Publication Date: 2025-01-21NINGBO JINJI STRONG MAGNETIC MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311494090.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-10
Publication Date
2025-01-21
Estimated Expiration
2043-11-10

AI Technical Summary

Technical Problem

Existing lanthanum cerium-containing magnets still need to add heavy rare earth elements to high performance products, resulting in high production costs and limited market applications. The addition of high-abundance rare earth elements will reduce the coercivity of the magnet.

Method used

By rationally controlling the composition of the permanent magnet, especially doping with Nb and Zr elements, the grain growth is suppressed, the grain boundary phase distribution is optimized, and the Nb-B, Zr-B phase and Re6Fe13M phase are formed, thereby improving the coercive force of the magnet. .

Benefits of technology

Without adding heavy rare earth elements, high-performance lanthanum-cerium-containing magnets can be obtained, reducing production costs, broadening market applications, and improving the coercive force and squareness of the magnets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117747233B_ABST
    Figure CN117747233B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of permanent magnetic materials, and relates to a heavy rare earth-free high-performance lanthanum-cerium rare earth permanent magnet and a manufacturing method thereof. The chemical composition of the lanthanum-cerium rare earth permanent magnet is expressed as: [(R1) 1‑x (R2) x ] a M1 b M2 c M3 d B e Fe 1‑a‑b‑c‑d‑e , wherein: 10%≤x≤25%, 29.5%≤a≤32.5%, 1%≤b≤2%, 0.5%≤c≤1%, 0%<d<2.5%, 0.85%≤e≤0.95%, wherein R1 is one or both of Pr and Nd, R2 is one or both of La and Ce, M1 is Cu and Ga, M2 is Nb and Zr, and M3 is one or more of Al, Co, and Mn. The present invention reasonably controls the composition of the permanent magnet to obtain a high-performance lanthanum-cerium magnet without adding heavy rare earth elements, effectively reduces the production cost of the magnet, and broadens the application of the lanthanum-cerium magnet in the market.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of permanent magnetic materials and relates to a heavy rare earth-free high-performance lanthanum-cerium-containing rare earth permanent magnet and a manufacturing method thereof. Background Art

[0002] NdFeB permanent magnet material is known as the "King of Magnets" due to its extremely high magnetic energy product, coercive force and energy density. It is widely used in computer hardware drive devices, various household appliances, electroacoustic equipment, multimedia equipment, electronic instruments, meters, medical equipment, industrial motors, wind turbines, as well as automotive sensors, electric vehicles and hybrid vehicles drive motors and other fields.

[0003] In recent years, as the market demand for NdFeB has gradually become saturated, the prices of rare earth raw materials such as praseodymium, neodymium, and dysprosium have increased. For the purpose of cost requirements and balanced resource utilization, sintered NdFeB magnets containing lanthanum and cerium have been widely used in the market, and competition has become increasingly fierce. However, the addition of high-abundance rare earth elements lanthanum and cerium will significantly reduce the coercive force of the magnet. At present, lanthanum-cerium magnets that can be achieved without the addition of heavy rare earths are mainly used in low-performance products in the industry. For products with high performance requirements, a certain proportion of heavy rare earth elements still need to be added, and the production cost is relatively high. Therefore, there is an urgent need for a lanthanum-cerium magnet that can reasonably utilize high-abundance rare earth resources, does not add heavy rare earth elements, and has high performance, as well as a preparation method for such a magnet. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a heavy rare earth-free high-performance lanthanum-cerium rare earth permanent magnet and a method for manufacturing the same. By reasonably controlling the composition of the permanent magnet, a high-performance lanthanum-cerium magnet can be obtained without adding heavy rare earth elements, thereby effectively reducing the production cost of the magnet and broadening the application of the lanthanum-cerium magnet in the market.

[0005] One object of the present invention is achieved by the following technical solutions:

[0006] A heavy rare earth-free high-performance lanthanum-cerium rare earth permanent magnet, the chemical composition of the lanthanum-cerium rare earth permanent magnet is expressed as:

[0007] [(R1) 1-x (R2) x ] a M1 b M2 c M3 d B e Fe 1-a-b-c-d-e ,

[0008] Among them: 10%≤x≤25%, 29.5%≤a≤32.5%, 1%≤b≤2%, 0.5%≤c≤1%, 0%<d<2.5%, 0.85%≤e≤0.95%, wherein R1 is one or two of Pr and Nd, R2 is one or two of La and Ce, M1 is Cu and Ga, M2 is Nb and Zr, and M3 is one or more of Al, Co and Mn.

[0009] x is the percentage of the mass of R2 to the total mass of R1 and R2, and a, b, c, d, and e are the percentages of the mass of the corresponding elements to the mass of the permanent magnet.

[0010] Preferably, in the lanthanum-cerium rare earth permanent magnet, Nb, Zr, Cu, and Ga satisfy the following relationship:

[0011] When 0.5%≤Nb+Zr≤0.7%, 1%≤Cu+Ga≤1.5%;

[0012] When 0.7%<Nb+Zr≤1%, 1.5%<Cu+Ga≤1.8%.

[0013] By doping with Nb and Zr elements, grain growth is inhibited, grain size uniformity is improved, grain boundary phase distribution is optimized, and grain boundary phase aggregation is reduced. At the same time, Nb, Zr and grain boundaries react with boron to form Nb-B and Zr-B phases, and doped Cu and Ga elements are more likely to enter the grain boundaries to form Re6Fe 13 M phase (M here refers to Cu and / or Ga) instead of entering the main phase grains, thereby effectively improving the coercivity of the magnet. As the doping ratio of Nb and Zr elements increases, a higher content of Cu and Ga elements is required to form Re6Fe 13 M phase.

[0014] Optionally, in the lanthanum-cerium rare earth permanent magnet, the content of Nb and Zr is 0.5-0.7%.

[0015] Preferably, in the lanthanum-cerium rare earth permanent magnet, the ratio of Nb content to Zr content is 1 to 5:1; further preferably, the ratio of Nb content to Zr content is 2 to 3:1.

[0016] Optionally, in the lanthanum-cerium rare earth permanent magnet, the content of Cu and Ga is 1-1.5%.

[0017] Preferably, in the lanthanum-cerium rare earth permanent magnet, the ratio of Ga content to Cu content is 1 to 3:1; more preferably, the ratio of Ga content to Cu content is 1 to 1.5:1.

[0018] Another object of the present invention is achieved by the following technical solutions:

[0019] A method for preparing a heavy rare earth-free high-performance lanthanum-cerium rare earth permanent magnet comprises the following steps: batching, smelting and casting to obtain alloy sheets, hydrogen crushing to obtain coarse powder, stirring the coarse powder, jet milling to obtain fine powder, stirring the fine powder, molding, sintering and aging.

[0020] Preferably, the melting temperature is 1420-1460° C., the casting temperature is 1410-1440° C., and the thickness of the alloy sheet is 0.15-0.4 mm.

[0021] Preferably, in the step of obtaining coarse powder by hydrogen decomposition, the dehydrogenation treatment temperature is 300-450° C. and the time is 180-300 min.

[0022] According to the chemical composition of the lanthanum-cerium rare earth permanent magnet of the present invention, the conventional dehydrogenation temperature is not used in the dehydrogenation process, and the dehydrogenation temperature used is 300-450°C. The hydrogen content of the powder after hydrogen decomposition is higher than that of the conventional dehydrogenation content, which can improve the oxidation resistance and molding orientation in the production process to a certain extent. In addition, the present invention adopts a lower dehydrogenation temperature to inhibit the formation of soft magnetic phases, avoid the existence of soft magnetic phases in the ferromagnetic phase at the grain boundary, and affect the coercive force and squareness of the magnet.

[0023] Preferably, the particle size of the coarse powder obtained by hydrogen rupture is 200-300 μm.

[0024] Preferably, the coarse powder is stirred at a speed of 10 to 15 rpm / min for 1 to 3 hours.

[0025] Preferably, 0.03-0.08% by weight of zinc stearate powder with an average particle size of 1-20 μm is added to the coarse powder during stirring. The addition of a solid agent improves the anti-oxidation property and fluidity of the powder.

[0026] Preferably, in the step of obtaining fine powder by air jet milling, 15-20 ppm of oxygen is introduced during air jet milling to pre-passivate the magnet powder, reduce the probability of oxidation, and improve the magnetic properties of the sintered NdFeB magnet.

[0027] Preferably, the particle size of the fine powder obtained by jet milling is 2.0-4.0 μm.

[0028] Preferably, the fine powder is stirred at a speed of 10 to 15 rpm / min for 1 to 3 hours.

[0029] Preferably, 0.03-0.08% by mass of liquid antioxidant and 0.02-0.06% by mass of gasoline are added to the fine powder during stirring.

[0030] Preferably, the molding step comprises: orientation molding in a magnetic field of 1.5-2.0 T under nitrogen protection.

[0031] Preferably, the sintering temperature is 1000-1200° C. and the time is 3-10 hours, wherein the temperature of the dehydrogenation stage during the heating process is 860-880° C. and the time is 4-8 hours.

[0032] Preferably, the aging is performed by graded aging, with the first aging temperature being 800-900°C for 2-5 hours, and the second aging temperature being 400-600°C for 3-8 hours.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention controls the element composition and content of lanthanum-cerium magnets to obtain high-performance lanthanum-cerium magnets without adding heavy rare earth elements, effectively reducing the production cost of magnets and broadening the application of lanthanum-cerium magnets in the market;

[0035] (2) The present invention optimizes the magnet structure by combining the component content and the preparation method, so that the grain boundaries of the magnet are evenly wrapped by the rare earth-rich phase, achieving better grain boundary phase coverage, playing a role in de-exchange coupling, and can achieve magnetic hardening, thereby achieving the purpose of improving the intrinsic coercive force of the NdFeB magnet;

[0036] (3) Solved the problem of poor performance consistency in the industrial production process due to the decrease in sintering temperature of lanthanum-cerium magnets caused by the addition of cerium;

[0037] (4) In the magnet preparation process of the present invention, the dehydrogenation temperature is lowered to increase the hydrogen content in the magnetic powder production process, thereby improving the oxidation resistance and molding orientation of the magnetic powder; at the same time, the presence of the soft magnetic phase in the ferromagnetic phase at the grain boundary is avoided, thereby ultimately improving the coercive force and squareness of the magnet. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The SEM images and EPMA point scanning diagrams of the magnets of Example 1 and Example 2, wherein (a) is the SEM image and EPMA point scanning diagram of the magnet of Example 1, and (b) is the SEM image and EPMA point scanning diagram of the magnet of Example 2.

[0039] Figure 2 The SEM images and EPMA point scanning diagrams of the magnets of Examples 9 and 10 are shown, wherein (a) is the SEM image and EPMA point scanning diagram of the magnet of Example 9, and (b) is the SEM image and EPMA point scanning diagram of the magnet of Example 10.

[0040] Figure 3 These are SEM images and EPMA point scanning diagrams of the magnets of Example 20 and Example 21, wherein (a) is the SEM image and EPMA point scanning diagram of the magnet of Example 20, and (b) is the SEM image and EPMA point scanning diagram of the magnet of Example 21. DETAILED DESCRIPTION

[0041] The technical scheme of the present invention is further described below by specific examples and accompanying drawings. It should be understood that the specific examples described herein are only used to help understand the present invention and are not intended for specific limitations of the present invention. The accompanying drawings used herein are only for better illustrating the disclosure of the present invention and do not have a limiting effect on the scope of protection. If not otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used raw materials in the art, and the methods used in the embodiments are all conventional methods in the art.

[0042] The liquid antioxidant used in the following examples and comparative examples is a type C antioxidant provided by Ningbo Haotian Rare Earth Chemical Co., Ltd.

[0043] Example 1

[0044] The chemical composition of the sintered NdFeB magnet of this embodiment is expressed as:

[0045] [(Pr 20% Nd 80% ) 78.3% (Ce) 21.7% ] 32.2% Cu 0.5% Ga 0.5% Nb 0.45% Zr 0.2% Al 0.8% Co 1% B 0.9% Fe 63.45% .

[0046] The sintered NdFeB magnet of this embodiment is obtained by the following preparation method:

[0047] The ingredients are prepared according to the weight percentage of each component, and the raw materials are placed in the crucible in order from high to low melting points. The furnace is evacuated to below 4Pa; then argon is filled into the furnace to make the pressure in the furnace reach 28kPa. After the iron rod is immersed in the molten steel, refining begins for 12 minutes, heating to 1460℃, and then the alloy liquid temperature is reduced to 1430℃ for casting. The copper roller speed is adjusted to 28r / min, and casting is carried out according to the system program, and finally an alloy sheet with a thickness of 0.3mm is obtained;

[0048] The alloy sheet is subjected to hydrogen absorption treatment under a hydrogen pressure of 0.09MPa. The change in the internal pressure of the reactor within 10 minutes does not exceed 0.5%, indicating that the hydrogen absorption is completed. After the hydrogen absorption is completed, the vacuum is evacuated and the temperature is heated to 400°C for 5.5 hours. 0.05% of the weight of the coarse powder and the average particle size of 5μm is added to the coarse powder, and stirred for 1 hour; 20ppm of oxygen is introduced, and the stirred coarse powder is air-milled into fine powder with an average particle size of 2.8μm. 0.05% of the weight of the fine powder is liquid antioxidant and 0.04% of the weight of the fine powder is gasoline, and stirred for 3 hours;

[0049] Under nitrogen protection, the fine powder was oriented and formed in a magnetic field of 1.8 T, heated to 875°C for dehydrogenation for 6 hours, then heated to 1065°C for sintering for 5 hours, aged at 900°C for 2.5 hours, and then aged at 485°C for 4.5 hours, and argon gas was introduced for air cooling.

[0050] The weight percentages of the components of Examples 2 to 19 and Comparative Examples 1 to 5 are shown in Table 1, and the preparation method is the same as that of Example 1.

[0051] Table 1 Composition of sintered NdFeB magnets of Examples 1-19 and Comparative Examples 1-5

[0052]

[0053]

[0054] The magnetic properties measurement samples were prepared by wire cutting, coreless grinding and end grinding. The cylinder was tested at room temperature (20°C) using a NIM-62000 demagnetization curve tester to obtain the magnetic properties of the sintered NdFeB magnets prepared in Examples 1-19. The test results are shown in Table 2.

[0055] Table 2 Magnetic properties of sintered NdFeB magnets of Examples 1-19

[0056] Example Remanence(kGs) Intrinsic coercivity (kOe) Squareness(%) 1 12.15 18.02 96.7 2 12.32 16.24 98.2 3 12.21 17.42 97.6 4 12.16 18.31 97.4 5 12.12 17.98 93.7 6 12.08 18.42 95.9 7 12.02 18.63 95.1 8 12 18.15 93.1 9 12.28 16.73 96.7 10 11.91 17.24 92.8 11 12.14 17.76 93.6 12 12.16 17.52 96.3 13 11.98 18.98 96.3 14 12.02 18.02 94.8 15 11.88 18.47 88.9 16 12.05 18.12 96.5 17 11.95 18.76 92.3 18 11.91 18.67 92.1 19 12.05 18.27 96.8 Comparative Example 1 12.45 16.45 94.8 Comparative Example 2 12.31 14.83 97.4 Comparative Example 3 12.19 17.35 95.3 Comparative Example 4 12.23 16.98 97.4 Comparative Example 5 12.75 13.59 96.1

[0057] Comparison of Example 1, Example 2, Example 6, Example 7, Example 8, and Comparison of Example 13, Example 14, and Example 15 shows that within the corresponding Nb+Zr total content range, too low Cu+Ga total content will lead to low coercivity, because there is not enough Cu and Ga elements to form R6Fe 13 M phase; if the total content of Cu+Ga is too high, the coercivity will be low and the squareness will also be poor. There is not enough Fe element at the grain boundary to form R6Fe with Cu+Ga. 13 M phase, and excessive doping of Cu and Ga elements causes grain boundary phase aggregation, which deteriorates the squareness.

[0058] The magnet microstructures of the sintered NdFeB magnets obtained in Example 1 and Example 2 were observed using SEM. Figure 1 (a) Figure 1 As shown in (b), it can be seen that the NdFeB magnet obtained in Example 1 has a more uniform and continuous distribution of grain boundary phases and a thicker grain boundary phase thickness than that in Example 2. Figure 1 (a) Figure 1 (b) SEM image and point scanning schematic diagram, the composition quality ratio is shown in Table 3:

[0059] Table 3

[0060]

[0061] It can be seen from the data in Table 3 that when the amount of Cu+Ga added in Experiment 2 is small, the content of Cu, Ga and Fe in the grain boundary phase is lower than that in Experiment 1, and R6Fe is not effectively formed. 13 M phase, and the continuity and clarity of the grain boundary phase distribution are not as good as those in Example 1.

[0062] Comparative Examples 1, 3, 4, 5, 13, 16, and 17, when the corresponding total content of Nb+Zr and the total content of Cu+Ga are appropriate, the Ga / Cu ratio is too low, and the grain boundary phase forms Re6Fe 13 Ga ratio relative to Re6Fe 13 Cu is lower. The former, as a hard magnetic phase in the grain boundary phase, has a better effect on suppressing coupling between grains than the latter, and obtains a higher coercive force. However, when the Ga / Cu ratio reaches a certain ratio, the improvement in the coercive force of the magnet is not particularly obvious. Combined with the price difference between Ga and Cu elements, the Ga / Cu content ratio needs to be controlled within a certain range.

[0063] Comparing Example 1, Example 9 and Example 10, within the corresponding Cu+Ga content range, the total Nb+Zr content is too low, the Nb-B and Zr-B phase ratios are relatively low, and there is not enough Fe content to form R6Fe with Cu and Ga. 13 M phase, resulting in low coercivity; if the total content of Nb+Zr is too high, it will lead to the presence of too many Fe-containing ferromagnetic phases at the grain boundaries, resulting in a decrease in the coercivity of the magnet and a significant deterioration in the squareness.

[0064] The sintered NdFeB magnets obtained in Example 9 and Example 10 were observed by SEM for their microstructure. Figure 2 (a) Figure 2 (b) SEM image and point scanning schematic diagram, the composition quality ratio is shown in Table 4:

[0065] Table 4

[0066]

[0067] It can be seen from the data in Table 4 that when the amount of Nb+Zr added is low, the proportion of Cu, Ga, and Fe is small, and the main phase formed is Nd-rich phase, and no R6Fe is formed. 13 M phase; when the amount of Nb+Zr added is too high, the content of Cu, Ga, and Fe is high, and R6Fe is formed. 13 At the same time as the M phase, a certain proportion of ferromagnetic phase is formed and distributed at the grain boundaries.

[0068] Comparative Example 1, Example 11, Example 12, and Comparative Example 13, Example 18, Example 19, when the corresponding total Nb+Zr content and Cu+Ga total content are appropriate, a too low Nb / Zr ratio will require a higher sintering temperature for the magnet to be sintered densely, which will cause grain boundary phase aggregation and affect the coercive force and squareness; a too high Nb / Zr ratio will weaken the grain growth inhibition effect, causing the grains to grow easily and become uneven in size.

[0069] Compared with Example 1 and Comparative Examples 1-5, in the case where Nb and / or Zr, and Cu and / or Ga are missing, the coercive force and squareness of the magnet are greatly reduced.

[0070] Embodiment 20

[0071] During the preparation process of the sintered NdFeB magnet of Example 20, after the hydrogen absorption is completed, Example 20 is evacuated and heated to 350° C. and kept warm for 5.5 hours. The other steps are the same as those of Example 1.

[0072] Embodiment 21

[0073] During the preparation process of the sintered NdFeB magnet of Example 21, after the hydrogen absorption is completed, Example 22 is heated to 550° C. and kept warm for 5.5 hours while evacuating the vacuum. The other steps are the same as those of Example 1.

[0074] Embodiment 22

[0075] During the preparation process of the sintered NdFeB magnet of Example 222, after the hydrogen absorption is completed, Example 22 is evacuated and heated to 350°C and kept warm for 5.5 hours. The other steps are the same as Example 1.

[0076] Embodiment 23

[0077] During the preparation process of the sintered NdFeB magnet of Example 23, after the hydrogen absorption is completed, Example 23 is evacuated and heated to 550° C. and kept warm for 5.5 hours. The other steps are the same as those of Example 1.

[0078] The magnetic properties measurement samples were prepared by wire cutting, coreless grinding and end grinding. The cylinder was tested at room temperature (20°C) using a NIM-62000 demagnetization curve tester to obtain the magnetic properties of the sintered NdFeB magnets prepared in Examples 20-23. The test results are shown in Table 5.

[0079] Table 5 Magnetic properties of sintered NdFeB magnets of Examples 20-23

[0080] Example Remanence(kGs) Intrinsic coercivity (kOe) Squareness(%) 20 12.12 18.34 97.5 21 12.26 17.35 92.5 22 11.96 19.25 96.8 23 12.09 18.11 91.7

[0081] Comparative Examples 1, 20, 21 and 13, 22 and 23 show that the coercive force of the magnet decreases with increasing dehydrogenation, the remanence increases with increasing dehydrogenation temperature, and the squareness decreases with increasing dehydrogenation temperature. If the magnet of the present invention is dehydrogenated at a normal dehydrogenation temperature of 450 to 600°C, a ferromagnetic intergranular phase is formed in the magnet grain boundary phase, resulting in increased remanence, decreased coercive force and deteriorated squareness.

[0082] The sintered NdFeB magnets obtained in Example 20 and Example 21 were observed by SEM for their microstructures. Figure 3 (a) Figure 3 As shown in (b), Figure 3 (a) Figure 3 (b) SEM image and point scanning schematic diagram, the composition quality ratio is shown in Table 6:

[0083] Table 6

[0084]

[0085] It can be seen from the data in Table 5 that the dehydrogenation temperature is too high and the hydrogen content of the casting is too low, which will increase the Fe element in the grain boundary phase of the final prepared magnet, and a certain proportion of ferromagnetic phase is formed and distributed at the grain boundary, which will lead to low coercive force of the magnet, poor squareness, and high remanence.

[0086] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0087] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0088] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A heavy rare earth-free high-performance lanthanum-cerium rare earth permanent magnet, characterized in that: The chemical composition of the lanthanum-containing cerium rare earth permanent magnet is expressed as: <h2 style=";text-align:left;direction:ltr">[(R1)<h2 style=";text-align:left;direction:ltr"> 1-x <h2 style=";text-align:left;direction:ltr"> (R2)<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> ]<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> M1<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> M2<h2 style=";text-align:left;direction:ltr"> c <h2 style=";text-align:left;direction:ltr"> M3<h2 style=";text-align:left;direction:ltr"> d <h2 style=";text-align:left;direction:ltr"> B<h2 style=";text-align:left;direction:ltr"> e <h2 style=";text-align:left;direction:ltr"> Fe<h2 style=";text-align:left;direction:ltr"> 1-a-b-c-d-e <h2 style=";text-align:left;direction:ltr"> , Wherein: 10%≤x≤25%, 29.5%≤a≤32.5%, 1%≤b≤2%, 0.5%≤c≤1%, 0%<d<2.5%, 0.85%≤e≤0.95%, wherein R1 is one or two of Pr and Nd, R2 is one or two of La and Ce, M1 is Cu and Ga, M2 is Nb and Zr, and M3 is one or more of Al, Co, and Mn; in the lanthanum-cerium rare earth permanent magnet, Nb, Zr, Cu, and Ga satisfy the following relationship: When 0.5%≤Nb+Zr≤0.7%, 1%≤Cu+Ga≤1.5%; When 0.7%<Nb+Zr≤1%, 1.5%<Cu+Ga≤1.8%.

2. The heavy rare earth-free, high-performance, lanthanum-containing, cerium-containing rare earth permanent magnet according to claim 1, characterized in that: In the lanthanum-cerium rare earth permanent magnet, the ratio of Nb content to Zr content is 1-5:

1.

3. The heavy rare earth-free, high-performance, lanthanum-containing, cerium-containing rare earth permanent magnet according to claim 1, characterized in that: In the lanthanum-cerium rare earth permanent magnet, the ratio of Ga content to Cu content is 1-3:

1.

4. The heavy rare earth-free, high-performance, lanthanum-cerium-containing rare earth permanent magnet according to claim 1, characterized in that: The content of Nb and Zr is 0.5~0.7%, and the content of Cu and Ga is 1~1.5%.

5. The method for preparing a heavy rare earth-free high-performance lanthanum-cerium rare earth permanent magnet according to claim 1, characterized in that: The following steps are involved: The process includes batching, smelting and casting to obtain alloy sheets, hydrogen crushing to obtain coarse powder, mixing the coarse powder, jet milling to obtain fine powder, mixing the fine powder, molding, sintering and aging.

6. The preparation method according to claim 5, characterized in that: In the step of obtaining coarse powder by hydrogen decomposition, the dehydrogenation treatment temperature is 300-450°C and the time is 180-300 min.

7. The preparation method according to claim 5, characterized in that: The molding step comprises: orientation molding in a magnetic field of 1.5-2.0T under nitrogen protection.

8. The preparation method according to claim 5, characterized in that: The sintering temperature is 1000~1200℃, and the time is 3~10h. During the heating process, the temperature of the dehydrogenation stage is 860~880℃, and the time is 4~8h.

9. The preparation method according to claim 5, characterized in that: The aging process adopts graded aging. The first aging temperature is 800~900℃, the time is 2~5h, and the second aging temperature is 400~600℃, the time is 3~8h.

Citation Information

Patent Citations

  • Rare earth permanent magnet alloy and preparation method thereof

    CN116844812A